Association between per- and polyfluoroalkyl substances exposure and blood pressure: From epidemiological evidence to mechanistic insights - Ziwen An; Yayuan Mei; Zhenzhen Tan; Zexuan Jiang; Xiuli Zeng; Longfei Li; Zheyuan Liu; Haiyan Shi; Jing Li; Wenjing Duan; Yiming Zhu; Mingmei Guo; et al. (Ecotoxicology and Environmental Safety)
Exposure to per- and polyfluoroalkyl substances (PFASs) is associated with hypertension, potentially involving inflammation; however, the specific correlations and mechanisms remain unclear. This study included 2801 adults from Hebei Province, China. We employed multiple linear regression and quantile g-computation models to examine the effects of plasma PFASs on systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), and pulse pressure (PP). Stratified analyses identified susceptible populations. Restricted cubic splines (RCS) explored dose-response relationships, and receiver operating characteristic (ROC) analysis evaluated the ability of blood pressure indicators to differentiate PFASs concentrations. Mediation analysis investigated the role of inflammatory cells, while bioinformatics analyses explored potential mechanisms. Specifically, PFOA was positively correlated with DBP (0.45 %, 95 % CI: 0.08 %, 0.82 %) and MAP (0.35 %, 95 % CI: 0.02 %, 0.68 %), while a positive association was found between PFDA and DBP (0.37 %, 95 % CI: 0.01 %, 0.73 %). In subgroup analyses, stronger correlations were found in more susceptible groups; for example, 6:2 Cl-PFESA was positively correlated with SBP (0.71 %, 95 % CI: 0.14 %, 1.29 %) in smokers. A monotonic dose-response relationship was observed for PFOA and MAP. ROC analysis indicated that DBP effectively distinguished PFOA and PFDA concentrations. Mediation analysis found monocyte percentages and the lymphocyte/monocyte ratio, as significant mediators in the PFASs-blood pressure relationship. Bioinformatics suggested that inflammation mediated by pattern recognition receptors (PPRs), particularly Macrophage-induced type C lectin (Mincle), may be a potential mechanism. PFASs, especially PFOA and PFDA, have significant hypertensive effects, with inflammation mediated by PPRs likely serving as a molecular mechanism.